PERAN ASAS CABOTAGE DI INDONESIA DALAM RANGKA MENGHADAPI KONSEP 21ST MARITIME SILK ROAD - Arumadanti Poerwanto; Anan Chandrawulan; Purnama Trisnamansyah (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Facing the liberalization of trade and services in international trade, further in the development of the 21stMaritime Silk Road concept that aims to improve connectivity and open the widest trade routes, making tariff rates as one of the factors to win the competition. Meanwhile, the existence of the cabotage principle which prevents foreign sea transportation from carrying out transportation activities in Indonesian waters is not in line with the concept of the 21st Maritime Silk Road. The purpose of this study was made to determine the role of Cabotage Principle in the midst of Indonesia’s commitment in facing the MSR’s concept. Based on the results of the study, the consistency in implementing Cabotage Principle in Indonesia will eventually supports Indonesia’s commitment in the concept of 21stMaritime Silk Road. keyword: Cabotage Policy, 21stMaritime Silk Road